Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kabupaten Lombok Tengah Tahun 2011-2020 - Lalu Irvan Maulana; Muhammad Faisal Abdullah; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine how the influence of the tourism sector on the local revenue of Central Lombok Regency in 2011-2020. The analytical tool used is processed time series data by testing the hypothesis of Multiple Regression Analysis, Classical Assumption Test, F Test, T Test, R Test. The results show that domestic tourists have an insignificant negative effect with a coefficient value of -0.049960 and a probability value of 0.5449 . Foreign tourists have a significant positive effect with a coefficient value of 0.123156 and a probability of 0.0256. Accommodation has a significant positive effect with a coefficient value of 692.4411 and a probability of 0.0363 on Regional Original Income in Central Lombok Regency in 2011-2020